The Effect of Using Wizard Liz’s Content on Students’ Listening Comprehension Skills at Ninth Grade Students of SMPN 1 Sepatan-Tangerang - Noer, Vanyssa Dwiana; arjulayana, Arjulayana; Anggraini, Diah Retno (Globish: An English-Indonesian Journal for English, Education, and Culture, 2025)
Listening comprehension is a crucial skill that significantly affects one's ability to communicate effectively in both professional and social contexts. To enhance students' listening abilities, many educators employ various methods and media, including utilizing YouTube videos from creators like The Wizard Liz. This research employed two types of assessments: a pre-test and a post-test. The study's participants were ninth-grade students from SMPN 1 Sepatan-Tangerang. Hypothesis testing was conducted using the Mann-Whitney test, where the null hypothesis (Ho) is rejected and the alternative hypothesis (H1) is accepted if the significance value is below 0.05. In the statistical analysis of Students' Listening skill results in the post-test, the value of Sig. (2-tailed) = 0.00 < 0.05 is obtained. Based on the data, it can be concluded that "H1 is accepted" and "H0 is rejected." Specifically, "H1 posits that there is a significant difference in students' listening skills when using The Wizard Liz's video compared to not using it," while "H0 suggests that there is no significant difference in students' listening skills between using The Wizard Liz's video and not using it. It can be concluded that the use of The Wizard Liz’s video as a learning medium has an effect on the listening ability of ninth-grade students of SMPN 1 Sepatan-Tangerang. Students teaching and learning activities using The Wizard Liz’s video media found that this media helped students improve their English language skills, especially in improving students' listening skills and helping students acquire new vocabulary.